IDDF2019-ABS-0133 Routinely available noninvasive tests discriminate advanced fibrosis due to NASH in the phase 3 STELLAR trials of the ASK1 inhibitor selonsertib. (June 2019) - Wong, Vincent Wai-Sun; Anstee, Quentin; Lawitz, Eric; Alkhouri, Naim; Romero-Gomez, Manuel; Okanoue, Takeshi; Trauner, Michael; Kersey, Kathryn; Li, Georgia; Subramanian, Mani; Myers, Robert; Djedjos, Stephen; et al.
Abstract : Background: Liver biopsy is currently the reference standard for fibrosis staging, but is an invasive procedure with limitations. There are a major unmet need for accurate, readily available noninvasive tests (NITs) to identify patients with advanced fibrosis due to NASH. Our aim is to describe the performance of NITs using the baseline data from the Phase 3 STELLAR studies of the ASK1 inhibitor selonsertib (SEL). Methods: The STELLAR studies (NCT03053050 and NCT03053063 ) enrolled patients with bridging fibrosis (F3) or compensated cirrhosis (F4) due to NASH (NAFLD Activity Score [NAS] ≥3). Baseline liver biopsies were centrally read according to the NASH CRN fibrosis classification and noninvasive markers of fibrosis, including the NAFLD fibrosis score (NFS), Fibrosis-4 (FIB-4) index, Enhanced Liver Fibrosis (ELF) test, and liver stiffness (LS) by transient elastography (TE; FibroScan®) were measured. The performance of these tests to discriminate advanced (F3-F4) fibrosis was evaluated using AUROCs with 5-fold cross-validation repeated 100x. Optimal thresholds for F3-F4 fibrosis were selected based on the literature. Data presented are from an interim analysis on 1 May 2018. Results: A total of 4467 patients (median age 58 years, 55% women, 72% Caucasian, 59% with diabetes) were screened. In the 3220 with evaluable histology, median biopsy length was 2.0 cm, 8% F0, 9% F1, 13% F2, 31% F3, 40% F4, 59% with NAS ≥5. Median values of NFS, FIB-4, ELF, and LS by TE increased with worsening fibrosis (-0.962/1.19/9.21/8.8 kPa in F0-F2 vs 0.342/2.20/10.39/16.5 kPa in F3-F4 respectively). AUROCs ranged from 0.75 to 0.80 to discriminate advanced fibrosis (table 1 ). When tests were combined, performance characteristics improved and PPVs ≥98% were possible. Conclusions: In these large, global phase 3 trials of SEL, routinely available NITs demonstrated acceptable diagnostic performance for the discrimination of advanced fibrosis due to NASH.